miRNA-Directed Regulation of the Main Signaling Pathways in Thyroid Cancer - Ramírez-Moya, Julia; Santisteban, Pilar (Frontiers in Endocrinology, 2019)
In the last two decades, great strides have been made in the study of microRNAs in development and in diseases such as cancer, as reflected in the exponential increase in the number of reviews on this topic including those on undifferentiated and well-differentiated thyroid cancer. Nevertheless, few reviews have focused on understanding the functional significance of the most up- or down-regulated miRNAs in thyroid cancer for the main signaling pathways hyperactivated in this tumor type. The aim of this review is to discuss the major miRNAs targeting proteins of the MAPK, PI3K and TGFβ pathways, to define their mechanisms of action through the 3’UTR regions of their target genes, and to describe how they affect thyroid tumorigenesis through their actions on cell proliferation, migration and invasion. Given the importance of miRNAs in cancer as diagnostic, prognostic and therapeutic candidates, a better understanding of this cross-talk might shed new light on the biomedical treatment of thyroid cancer.